KEANEKARAGAMAN ODONATA (Dragonflies) DI BEBERAPA PERSAWAHAN BERDASARKAN SEX RASIO ODONATA DEWASA DAN PANJANG TUBUH (INSTAR) NIMFA ODONATA - Irwandi Ansori (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The research on Odonata diversity was conducted in Antapani, Cigadung, Dago Pakar and Dago Pojok paddy fields located in Bandung. The objectives of the study were to identify Odonata species, to analyse the population dynamics and abundance of Odonata. Adults of Odonata were taken by sweeping net (depth 60 cm, Ø 30-38 cm), and nymphs were caught by sieve of the size of Ø 30 cm. The samples were done taken paddy growth. Adults. Two (2) families of adult Odonata were identified and consist of 4 species, i.eOrthetrum sabina (Libellulidae), Crocothemis servilia (Libellulidae), Neurothemis terminata (Libellulidae) and Anaciaeshna jaspidea (Aeshnidae). Three (3) species of nymphs Odonata were identified, i.e: Orthetrum sabina (Libellulidae), Crocothemis servilia (Libellulidae), and Anaciaeshna jaspidea (Aeshnidae). The result of this research showedthat Crocothemis servilia (Libellulidae) and Orthetrum sabina (Libellulidae) were dominant species in four research location. In the early  paddy growth (vegetatif phase to pregnant phase ~ 22 - 27 day) showed the highest number of Odonata (adult and nymph) compared with the other phase, by the time there will be a decrease in the population of Odonata. The sex ratio on adult Odonata show that male Odonata is more biggestthan Odonata female. The highest lenght of odonata nympha at vegetative and  primodial phase at the first stage of paddy growth and the lowest lenght at bunting, masak susu and masak penuh phase. Keywords : Odonata, Sex Rasio, Body Lenght (Instar)